2019
DOI: 10.3389/fmicb.2019.00057
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Inputs From Lactic Acid Bacteria and Their Bacteriocins as Alternatives to Antibiotic Growth Promoters During Food-Animal Production

Abstract: Resistance to antibiotics is escalating and threatening humans and animals worldwide. Different countries have legislated or promoted the ban of antibiotics as growth promoters in livestock and aquaculture to reduce this phenomenon. Therefore, to improve animal growth and reproduction performance and to control multiple bacterial infections, there is a potential to use probiotics as non-antibiotic growth promoters. Lactic acid bacteria (LAB) offer various advantages as potential probiotics and can be considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
255
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 426 publications
(318 citation statements)
references
References 225 publications
(255 reference statements)
2
255
0
9
Order By: Relevance
“…LAB are widely used as probiotics owing to their beneficial effects on human and animal health. 52,53 In the food and feed industry, probiotic LAB strains are normally selected using well-established, classical screening methods on the basis of criteria that relate to phenotypic traits and functional properties, such as safety, antimicrobial activity, and host colonization. 54 In this context, comparative genome analysis using next-generation sequencing technologies has brought new insights into the probiotic characterization of LAB, including a much better understanding of their interaction with immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…LAB are widely used as probiotics owing to their beneficial effects on human and animal health. 52,53 In the food and feed industry, probiotic LAB strains are normally selected using well-established, classical screening methods on the basis of criteria that relate to phenotypic traits and functional properties, such as safety, antimicrobial activity, and host colonization. 54 In this context, comparative genome analysis using next-generation sequencing technologies has brought new insights into the probiotic characterization of LAB, including a much better understanding of their interaction with immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that probiotic LGG microcapsules could inhibit E.coli bio lm formation without causing antibiotic resistance. Probiotics have many bene ts for human health and are used both therapeutically and in the food industry [9].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, production and consumption of animal products have largely increased [6]. In a future, this increase is expected to continue in order to meet the high demand for livestock products such as meat, milk, eggs, and fish, especially in industrialized countries [7][8][9].…”
Section: The Use Of Antibiotics In Animal Productionmentioning
confidence: 99%
“…To this end, they have been supplied in subtherapeutic doses to help livestock by improving growth rate, reducing mortality, and enhancing animal reproductive performance [15]. Antibiotics mostly employed in AGP applications include tetracyclines, ionophores, and penicillin's [9,16].…”
Section: The Use Of Antibiotics In Animal Productionmentioning
confidence: 99%